أصل المسألة: الاستعمال إذا لم ينقل الماء عن صفاته، فإنّه لا يؤثّر في تطهيره: If Usage Does Not Alter The Characteristics of Water, Then it Does Not Affect its Purifying Quality - Ousman Mbye (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This research investigates a key jurisprudential principle in the Mālikī school: “If usage does not alter the characteristics of water, then it does not affect its purifying quality.” The study emphasizes that water previously used to remove ritual impurity remains valid for purification, though its use is considered disliked when alternative water is available. If no other water exists, its use is not disliked. A minority opinion, however, prohibits such use, relying on Ibn al-Qāsim’s interpretation of Imām Mālik in al-Mudawwana.The study follows a structured methodology to clarify the principle. It begins by presenting the principle as stated by Mālikī scholars, then explains its meaning, sources, and textual formulations. It examines scholarly differences regarding the accepted narration, highlights the narrations on which the principle is built, and analyzes the reasoning behind preferring one narration over another. The research also explores how unaccepted narrations were addressed, evaluates the evidences supporting the principle, and outlines the positions of Mālikī scholars in both cases of consensus and disagreement. Where agreement exists, the study assesses its legal impact, and where disagreement appears, it analyzes the causes and consequences. Finally, it identifies possible exceptions to the principle, their evidences, and any rulings derived from them. By systematically addressing these points, the research provides a unique and original contribution to the study and service of the Mālikī school. Among the most prominent results of the research: It is permissible to perform ritual ablution and ritual purification with water used by a woman, if the use did not change any of its characteristics: its color, taste, or smell. Likewise, it is permissible to perform tayammum with soil that has been used for tayammum, if no impurity is seen in it.